Effective Parenting in the Preadolescent Years - Suzanna Smith (EDIS, 2012)
Effective parents show love by spending time with their young teen, showing a genuine interest in them. This 2-page Family Album Radio transcript was written by Suzanna Smith and published by the UF Department of Family Youth and Community Sciences, July 2012.